Odpowiedź :
Szczegółowe wyjaśnienie:
[tex] - 1 \frac{2}{3} \div ( - 0.5) = - \frac{5}{3} \div ( - \frac{1}{2} ) = - \frac{5}{3} \times ( - \frac{2}{1} ) = \frac{10}{3} = 3 \frac{1}{3} [/tex]
[tex] - 1 \frac{2}{10} \times 1 \frac{1}{4} = - \frac{12}{10} \times \frac{5}{4} = - \frac{3}{2} = - 1 \frac{1}{2} [/tex]
[tex]( { - 1 \frac{1}{2}) }^{2} = ( { - \frac{3}{2}) }^{2} = \frac{9}{4} = 2 \frac{1}{4} [/tex]
Odpowiedź:
[tex]-1\frac{2}{3} : -\frac{1}{2} = \frac{5}{3} * 2 = \frac{10}{3} = 3\frac{1}{3}[/tex]
[tex]-\frac{6}{5} *\frac{5}{4}=-3 * \frac{1}{2} = -\frac{3}{2} = -1\frac{1}{2}[/tex]
[tex](-1\frac{1}{2})^{2} = (-\frac{3}{2})^{2} = \frac{9}{4} = 2\frac{1}{4}[/tex]